Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.redox.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Nox4 NADPH oxidase contributes to smooth muscle cell phenotypes associated with unstable atherosclerotic plaques

Abstract: Plaque instability associated with acute coronary syndromes results in part from apoptosis and senescence of cells within the atherosclerotic (AS) lesion. Increased cellular oxidative stress has been proposed to contribute to plaque progression and changes in composition, leading to plaque instability. Our objective was to examine the role of NADPH oxidase in smooth muscle cell (SMC) phenotypes associated with an unstable plaque. Aortae were isolated from pre-lesion (8 weeks of age) and post-lesion (35 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 41 publications
2
45
0
1
Order By: Relevance
“…Interestingly patients with p47 phox hereditary deficiency had intermediate flow-mediated dilation and oxidative stress [28]. Changes in the NADPH oxidase system may contribute to smooth muscle cell phenotypes associated with unstable atherosclerotic plaques [29], and new therapeutic strategies for cardiovascular disease based on prevention of ROS production, include the development of less toxic and more selective NADPH oxidase inhibitors, allowing clarification of the role of each NADPH oxidase isoform and its potential use in clinical practice [16]. In this study we sought to investigate whether specific inhibition of NADPH oxidase decreases the progression of atheromatous plaques and reduces the pro-angiogenic mediators that lead to increase plaque risk for rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly patients with p47 phox hereditary deficiency had intermediate flow-mediated dilation and oxidative stress [28]. Changes in the NADPH oxidase system may contribute to smooth muscle cell phenotypes associated with unstable atherosclerotic plaques [29], and new therapeutic strategies for cardiovascular disease based on prevention of ROS production, include the development of less toxic and more selective NADPH oxidase inhibitors, allowing clarification of the role of each NADPH oxidase isoform and its potential use in clinical practice [16]. In this study we sought to investigate whether specific inhibition of NADPH oxidase decreases the progression of atheromatous plaques and reduces the pro-angiogenic mediators that lead to increase plaque risk for rupture.…”
Section: Discussionmentioning
confidence: 99%
“…67 Expression of EBP50 is elevated in SMC after the angioplasty. 68 71 Vendrov et al 24 showed that while knockout of Ncf1 gene, encoding for p47 phox , an essential regulatory subunit of both Nox1 and Nox2, is protective in young Apoe −/− mice, the effect is lost in aged animals. 24 Areas of aortic atherosclerotic lesions, staining with DHE, levels of DNA oxidative damage, or macrophage infiltration were similar in aged Apoe −/− and Apoe…”
Section: Smooth Muscle Cellsmentioning
confidence: 99%
“…Importantly, the role of p53 in premature aging is evident from several mouse studies where persistent low-level activation and increased expression, by ROS signalling, telomere erosion or DNA damage, promotes senescence or irreversible cell cycle arrest [137139]. In turn, vascular cell senescence is one proposed mechanism surrounding unstable atherosclerotic plaque progression [140]. The ability for p53 to control senescence is consistent with its function to restrain vascularized tumour development, but the precise role for maintenance of longevity requires further investigation [141].…”
Section: Role Of Ros Signalling In Proteins Involved In Agingmentioning
confidence: 99%